2010
DOI: 10.4067/s0718-16202010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Preference for oils with different types of genetic modifcations in Temuco, Araucanía Region, Chile

Abstract: Preference for oils with different types of genetic modifications in Temuco, Araucanía Región, Chile. Cien. Inv. Agr. 37(1):17-28. Considering that attitudes towards biotechnology depend on the type of modification used, a study was performed to determine the importance of the type of Genetic Modification (GM) in preferences for oil purchased by consumers in Temuco (Araucanía Region, Chile) and the existence of different market segments using a survey of 400 people. A conjoint analysis demonstrated that the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
2
4
0
1
Order By: Relevance
“…This result and the rejection of GM oil in Groups 1, 2 and 3 is consistent with studies conducted in North America that indicated a greater acceptance of nanotechnology than GM (Currall et al, 2006;Priest, 2006;Cobb and Macoubrie, 2004); this preference might be related to the perception of GM by many people as unnatural (Stampfli et al, 2010). Likewise, the rejection of GM oil confirms the results from previous studies conducted both in developed countries (O'Brien et al, 2012;Bellows et al, 2010;Terawaki, 2008) and in Chile (Schnettler et al, 2010(Schnettler et al, , 2008) that reported a greater consumer preference for foods without GM and a rejection of TF. Because the acceptance of foods produced with new technologies is directly associated with consumers' perception of the risks and benefits of the associated technology (Frewer et al, 2011;Rollin et al, 2011;Siegrist et al, 2008;Siegrist et al, 2007), these results suggest that the participants perceived GM products as riskier than those produced with nanotechnology; furthermore, this perception occurred despite the fact that a definition of nanotechnology, which included the potential benefits and risks associated with its use, was given before presenting the stimuli of the conjoint analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result and the rejection of GM oil in Groups 1, 2 and 3 is consistent with studies conducted in North America that indicated a greater acceptance of nanotechnology than GM (Currall et al, 2006;Priest, 2006;Cobb and Macoubrie, 2004); this preference might be related to the perception of GM by many people as unnatural (Stampfli et al, 2010). Likewise, the rejection of GM oil confirms the results from previous studies conducted both in developed countries (O'Brien et al, 2012;Bellows et al, 2010;Terawaki, 2008) and in Chile (Schnettler et al, 2010(Schnettler et al, , 2008) that reported a greater consumer preference for foods without GM and a rejection of TF. Because the acceptance of foods produced with new technologies is directly associated with consumers' perception of the risks and benefits of the associated technology (Frewer et al, 2011;Rollin et al, 2011;Siegrist et al, 2008;Siegrist et al, 2007), these results suggest that the participants perceived GM products as riskier than those produced with nanotechnology; furthermore, this perception occurred despite the fact that a definition of nanotechnology, which included the potential benefits and risks associated with its use, was given before presenting the stimuli of the conjoint analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Typically, results suggest that GM agri-food technology is associated with high perceived risks and relatively low perceived benefits (Frewer et al, 2011). This is why numerous studies have reported a greater consumer preference for foods without GM and a rejection of transgenic foods (TF) (O'Brien et al, 2012;Bellows et al, 2010;Schnettler et al, 2010Schnettler et al, , 2008Terawaki, 2008). However, there is also evidence of the existence of consumer groups with positive attitudes towards TF, but they are principally found in developing countries (De Steur et al, 2010;Kimenju and De Groote, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The lower frequency of daily milk consumption in Group 4 by the WA subsample seems to confirm that the preferences for GM foods are related to food consumption habits (Schnettler et al, 2010). The greater presence of people that did not know the meaning of an animal being GM in Group 1 of the WA subsample could partly explain the rejection of GM and the acceptance of cloning.…”
Section: Attribute and Levelsmentioning
confidence: 53%
“…According to the conjoint analysis (Table 3) for the entire sample, the attribute of greatest importance during the purchase process was the production technology, followed by the price, brand, fat content, and finally the package. The signs of the utility values indicate preference for milk from a conventional animal in keeping with previous studies that have evaluated the acceptance of GM foods (International Food Information Council, 2014;Lähteenmäki et al, 2003;Mucci et al, 2004;Siegrist, 2008;Schnettler et al, 2010Schnettler et al, , 2012 in both developed and developing countries, and cloned (Aizaki et al, 2011;Creative Research, 2008;International Food Information Council, 2008;Brooks & Lusk, 2010, 2011Saeed et al, 2015) in developed countries. Nevertheless, in the case of GM foods, it contradicts the results of studies carried out both in developing (Costa et al, 2000;Kimenju & De Groote, 2008;De Steur et al, 2010) and developed countries (Cox et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation